2009
DOI: 10.1073/pnas.0910439106
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of NF-κB activity through lysine monomethylation of p65

Abstract: NF-B is a key activator of inflammatory and immune responses with important pathological roles in cancer, heart disease, and autoimmune diseases. Transcriptional activity of NF-B is regulated by different posttranslational modifications. Here, we report a novel mechanism of NF-B regulation through lysine monomethylation by SET9 methyltransferase. Set9 specifically methylates p65 at lysine 37. Both TNF␣ and IL-1␤ treatments induced methylation of p65. Methylated p65 is restricted to the nucleus and this modific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
191
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(202 citation statements)
references
References 25 publications
6
191
5
Order By: Relevance
“…The RelA L1 loop, which is critical for nucleotide sequence recognition and binding, has been shown to be monomethylated at K37 by SET7/9 (12) and symmetrically dimethylated at R30 by PRMT5 (16). These modifications cause an increase in the RelA affinity to DNA and activate NF-κB, in contrast with the inhibitory asymmetric R30 dimethylation by PRMT1 identified in our study.…”
Section: (7)contrasting
confidence: 55%
See 1 more Smart Citation
“…The RelA L1 loop, which is critical for nucleotide sequence recognition and binding, has been shown to be monomethylated at K37 by SET7/9 (12) and symmetrically dimethylated at R30 by PRMT5 (16). These modifications cause an increase in the RelA affinity to DNA and activate NF-κB, in contrast with the inhibitory asymmetric R30 dimethylation by PRMT1 identified in our study.…”
Section: (7)contrasting
confidence: 55%
“…Recent work of several laboratories has identified methylation as another regulatory RelA modification that controls gene expression downstream of TNFα and IL-1β signaling. Several histone lysine methyltransferases, including SET7/9, SETD6, and NSD1, have been shown to both positively and negatively regulate NF-κB through direct monomethylation or dimethylation of distinct lysine residues in RelA (12)(13)(14)(15). Recent studies also have shown that RelA is methylated by the type II protein arginine methyltransferase 5 (PRMT5), which catalyzes the synthesis of ω-N Gmonomethylarginine (MMA) and symmetric ω-N G ,N′ G -dimethylarginine (SDMA) (16,17).…”
mentioning
confidence: 99%
“…2B), and we have not yet analyzed the methylation status of all of the lysine residues of p65 by MS. In addition to the methylation of K314/K315 discussed above (25), a recent report shows that K37 of p65 is also monomethylated by SET9 (29). Therefore, the possibility of additional methylation sites on p65 should be investigated in the future, as should the possibility that the p50 subunit may also be methylated.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 However, we and others showed that the recombinant Set7/9 failed to target nucleosomes for methylation, [6][7][8] suggesting that Set7/9 functions as a factor-specific KMTase. There have been several non-histone proteins reported as the substrates for Set7/9, including TAF10 (TATA box binding protein (TBP)-associated factor, 30 kDa), 9 oestrogen receptor a (ERa), 10 RelA, 11 PCAF (P300/CBP-associated factor), 12 Stat3, 13 Yap, 14 and Suv39h1. 15 However, in most cases the functional significance of this methylation is still not clear.…”
mentioning
confidence: 99%